Venecijaus Gyvenimas ir Cezario mirtis . Venecijus's Life and Death of Cezar - Lapisnkaite, Janina (Rupeikaite, Goda, 2002)
Duration: 00:54:00 Venecius is a Lithuanian peasant farmer just shy of fifty. From the time that his wife and children left him, he has lived on a remote farm, completely isolated from society. One day he bought a pig and named it Cezar. While he feeds and prepares it for slaughter, Cezar becomes more and more Venecius's companion and a witness to his loneliness. However, when the fattened pig reaches a weight of 80 kg, its fate is sealed. The film is a delicate balance between a melancholic documentary and humorous farce.